Cashmere quality of Raeini goats kept by nomads in Iran - Ansari-Renani, Hamid R.; Mueller, Joaquin Pablo; Rischkowsky, Barbara; Seyed Momen, S.M.; Alipour, O.; Ehsani, M.; Moradi, Sepehr (2017)
The income of the nomads in Kerman Province depends mainly on Raeini goats that produce meat, milk and cashmere. This paper assesses the cashmere quality and its variation in Raeini herds to determine the scope for improvement. In April 2010 fleece weights (FW) and midside fleece samples were taken from a total of 686 male and female cashmere goats of 1, 2 and 3 years of age belonging to 29 herds. The herds were randomly chosen in the summer grazing area of nomads within 20 km of the city of Baft, province of Kerman, South of Iran, the main cashmere producing area in Iran. Cashmere yield (CY) was determined from the weight of dehaired cashmere to weight of shorn fiber. Cashmere fibers were analyzed using an OFDA instrument. A general mixed linear model including sex, age and sex by age interaction as fixed effects and herd as random effect was used to analyze the data and measure the relationships between different cashmere characteristics and fleece attributes. The overall means ± standard deviations were for fleece weights (FW) 507 ± 183 g, cashmere yield (CY) 56.5 ± 12.2%, mean fiber diameter (MFD) 19.7 ± 1.5 μm, fiber diameter standard deviation (FDSD) 4.5 ± 0.6 μm, fiber curvature (FC) 62.9 ± 8.5°/mm and staple length (SL) 54.2 ± 7.0 mm, respectively. Herd effect was significant for all traits except for SL and sex by age effect was only significant for MFD. One year old males and females had finer cashmere than older goats. FW and FDSD were higher in males and CY and FC was higher in young animals. Pearson correlation between MFD and FC, FDSD and MFD, MFD and FW was −0.647, 0.399 and 0.211 respectively. Raeini cashmere is white, has an excellent SL and FC but is relatively coarse. Given the differences between and within herds there seems to be substantial scope to improve the commercial value of Raeini cashmere.